Pandemia de covid-2019: mudanças nos processos de aquisição de materiais para saúde no Brasil - SANTOS, Beatriz Batemarco dos Santos (2023)
Introduction: Covid-19 pandemics highlighted the need to reorganize health systems and rearrange strategies for public procurement, in order to guarantee the population's access to the health technologies for effective care, respecting legality, economic advantage, and transparency in public administration. Purpose: Evaluate public procurement of equipment and pharmaceuticals in pandemics in a comparative perspective of the period before and after declaration of “state of emergency”. Methods: Authors used Open access data available from Brazil’s Federal Government: Transparency Website, Public procurement Website, COVID-19 Procurement Website and Health Prices Database. We performed descriptive and comparative analysis of the data. Unit values of the items were updated according to the IPCA index. Nonparametric Mann-Whitney-Wilcoxon test was applied to compare unit prices of the items between before and after pandemic declaration. Results: We observed a 900% increase in the amount of electronic respiratory ventilators purchased from 2019 to 2020. 97.5% of the equipment were purchased using dispensing of bidding modality. No statistical difference was observed in the unit values of electronic respiratory ventilators when comparing both periods. We observed a statistically significant increase in unit prices of sedative and muscle relaxant drugs. We identified an average price increase for the following drugs: midazolam 5 mg/ml 10 ml (381.18%), propofol 10 mg/ml 10 ml (156.4%), atracurium 10 mg/ml 2.5 ml (97.5%), atracurium 10 mg/ml 2.5 ml (97.4%), suxamethonium 100 mg (91.3%), etomidate 2 mg/ml 10 ml (87.4%), and cisatracurium 2 mg/ml 10 ml (44.9%). Conclusions: In pandemics, public agencies have chosen to use dispensing of bidding for centralized and emergency acquisition of electronic respiratory ventilators, so they could attend public interest for new covid-19 ICU beds availability. We conclude that, in population terms, it was a significant increase in the unit values charged by public administration for most of the drugs used in clinical practice for the orotracheal intubation procedure after the covid-19 pandemic. The increase was not observed in values of electronic respiratory ventilators, indicating possible different dynamics of health equipment and pharmaceutical industries.